Mining Foundation of the Southwest Honors its 2005 Inductees (Society for Mining, Metallurgy & Exploration, 2005)
The 23rd annual American Mining Hall of Fame Awards Banquet sponsored by the Mining Foundation of the Southwest will be held at the Tucson Marriott University Park Hotel, Tucson, AZ on Saturday, Dec. 3, 2005. The Mining Foundation of the Southwest is a non-profit organization. It educates the public about the mineral industries and reports outstanding accomplishments in the fields of mining and the earth sciences. This year’s inductee, guest of honor and featured speaker at the banquet will be Pierre Lassonde, president of Newmont Mining and resident of the World Gold Council. He is one of Canada’s leading gold analysts.